Hubungan Kematangan Emosi dan Konformitas Teman Sebaya Dengan Kecenderungan Perilaku Agresif Pada Kelompok Remaja di Surabaya (Fakultas Psikologi Universitas 17 Agustus 1945 Surabaya, 2020)
The tendency of aggressive behavior is a form of behavior that has the purpose of hurting or hurting others, both physically and verbally which can be influenced by several internal factors such as emotional maturity and external factors namely peer conformity. The purpose of this study was to determine the relationship between emotional maturity (X¹), peer conformity (X²), and tendency for aggressive behavior (Y). Participants in this study were adolescent groups in Surabaya, amounting to 114 people. This research data was obtained by distributing questionnaires to subjects who met the participants' characteristics. This study uses a quantitative approach. The analysis technique uses the Spearman’s Rho test with the help of the Statistical Package for the Social Sciences (SPSS) program version 16.0 for windows. The results of this study indicate that 1) there is no significant negative relationship between emotional maturity and the tendency for aggressive behavior in adolescent groups in Surabaya. 2) there is no significant negative relationship between peer conformity and the tendency of aggressive behavior in adolescent groups in Surabaya. The conclusion of this study is that there is no relationship between emotional maturity and peer conformity with the tendency of aggressive behavior in adolescent groups in Surabaya.Keywords: Trends in Aggressive Behavior; Emotion Maturity; Peer Conformity